2011
DOI: 10.1111/j.1600-0781.2011.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

A single blind randomized clinical study: the efficacy of isotretinoin plus narrow band ultraviolet B in the treatment of psoriasis vulgaris

Abstract: In this randomized clinical trial, 39 patients with psoriasis vulgaris were randomized in two groups. Intervention group received narrow band ultraviolet B (NBUVB)+isotretinoin (0.5 mg/kg/day), control group received NBUVB+placebo. Psoriasis Area Severity Index (PASI) scoring was recorded at baseline and weeks 4, 10, and 14. Thirty-seven patients completed the study. According to recorded PASI scores the difference between efficacies of two treatments was not significant. Complete clearing was noticed in 14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
7
0
5
Order By: Relevance
“…Total DLQI scores range between 0 (no impairment) and 30 (maximum impairment). The 10 questions in the DLQI can be subdivided into six domains that relate to different aspects of a person's health-related QoL as follows: symptoms and feelings (questions 1, 2), daily activities (3,4), leisure (5,6), work/school (7), personal relationships (8,9) and treatment (10). Higher scores mean greater impairment of the patient's QoL (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total DLQI scores range between 0 (no impairment) and 30 (maximum impairment). The 10 questions in the DLQI can be subdivided into six domains that relate to different aspects of a person's health-related QoL as follows: symptoms and feelings (questions 1, 2), daily activities (3,4), leisure (5,6), work/school (7), personal relationships (8,9) and treatment (10). Higher scores mean greater impairment of the patient's QoL (17).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the relatively low dosage of isotretinoin (0.5 mg/ kg) used in the present study. In a randomized controlled trial assessing the efficacy of isotretinoin plus NBUVB in psoriasis, Mortazavi et al reported mild to moderate erythema, pruritus and nausea as side effects (8). None of their patients stopped treatment due to side effects.…”
Section: Side Effectsmentioning
confidence: 99%
“…18,19 Beberapa studi dan laporan kasus lain melaporkan keberhasilan kombinasi terapi isotretinoin oral dengan psoralen dan ultraviolet A (PUVA) atau UVB pada psoriasis berat dengan dosis 0,4-2 mg/kg/hari. [20][21][22] Hal yang sangat penting untuk diperhatikan pada terapi isotretinoin adalah efek samping obat yang biasanya timbul pada terapi jangka panjang. Efek samping yang dapat terjadi antatra lain efek teratogenik, penglihatan kabur, penutupan epifisis prematur, inflammatory bowel disease, pankreatitis, hepatitis toksik, pseudotumor serebri, depresi, keinginan bunuh diri, leukopenia, trombositopenia, keilitis, serotik, mata dan hidung kering, fotosensitif, rambut rontok, dan hipertrigliseridemia.…”
Section: Pembahasanunclassified
“…Los estudios en que se utiliza el acitretín en combinación con fototerapia (PUVA/UVB) han demostrado la clara superioridad del tratamiento combinado con estos dos agentes sobre cada uno de ellos como monoterapia, en casos de psoriasis en placas e, inclusive, en la forma pustulosa 3,31,36 .…”
Section: Tratamiento Combinado Con Retinoidesunclassified
“…Las principales ventajas de la combinación fueron: aceleración de la tasa de remisión de las lesiones; mejoría de las lesiones en casos de falla terapéutica de la monoterapia con retinoides o con fototerapia; y, disminución del número de las sesiones, con menor riesgo de efectos cancerígenos propios de la radiación, los cuales dependen claramente de la dosis 30,31,36 . Además, los retinoides orales han demostrado proteger contra el cáncer de piel 32 .…”
Section: Tratamiento Combinado Con Retinoidesunclassified